2009
DOI: 10.1063/1.3119212
|View full text |Cite
|
Sign up to set email alerts
|

Length control of He atmospheric plasma jet plumes: Effects of discharge parameters and ambient air

Abstract: The effects of various discharge parameters and ambient gas on the length of He atmospheric plasma jet plumes expanding into the open air are studied. It is found that the voltage and width of the discharge-sustaining pulses exert significantly stronger effects on the plume length than the pulse frequency, gas flow rate, and nozzle diameter. This result is explained through detailed analysis of the I-V characteristics of the primary and secondary discharges which reveals the major role of the integrated total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
63
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(75 citation statements)
references
References 48 publications
8
63
0
3
Order By: Relevance
“…A time lag (ΔtGIWs) is established between the zero-crossing point of the positive current impulse and the rising voltage edge. The corresponding ΔtGIWs in the case of negative impulse is negligible under our experimental conditions, which is in agreement with other published works [16,23,42]. Hereafter, the results section will refer to the peak value (IPeak) of the positive current impulse, its corresponding accumulated charge (Qmain, obtained through integration of the current impulse over time), and the time lag ΔtGIWs (see Figure 3b for definition).…”
Section: Methodssupporting
confidence: 77%
See 2 more Smart Citations
“…A time lag (ΔtGIWs) is established between the zero-crossing point of the positive current impulse and the rising voltage edge. The corresponding ΔtGIWs in the case of negative impulse is negligible under our experimental conditions, which is in agreement with other published works [16,23,42]. Hereafter, the results section will refer to the peak value (IPeak) of the positive current impulse, its corresponding accumulated charge (Qmain, obtained through integration of the current impulse over time), and the time lag ΔtGIWs (see Figure 3b for definition).…”
Section: Methodssupporting
confidence: 77%
“…As it was previously mentioned, the tuning of V p does not affect the ∆t GIWs of the negative impulse, which is clearly demonstrated in the right frame of Figure 4. Identical behaviors were remarked in other studies, as well concerning linear-field [16] and single-electrode [42] setups. Jarrige et al [16] observed via ICCD measurements that the secondary discharge appeared in the DBD at the end of the voltage pulse, without any evident formation of a second plasma "bullet".…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…In any plasma jet system, the gas flow rate plays a key role in defining the physical characteristics of the discharge; parameters such as gas temperature and particle diffusion are all strongly influenced by the gas flow [39,40]. By introducing the gas flow rate as the second control parameter, it is possible to create a map of dynamical regimes in the plane of the two control parameters.…”
Section: Two Parameter Analysismentioning
confidence: 99%
“…Stoffels et al developed a RF plasma jet called the "plasma needle," 10 which was extensively used in biomedical applications. 11 Among several other plasma jets that have been developed, [12][13][14][15][16] those which employ simple and nonexpensive voltage generators are attractive for biological or medical application not requiring a very strict control of the thermal load on the gas carrier. A comprehensive review, which gives a description of different plasma jet configurations and biomedical applications, was recently presented by Park et al 17 In particular, Li et al presented recently an atmospheric pressure jet driven by an a-c transformer operated at 50 Hz.…”
Section: And References Therein)mentioning
confidence: 99%